Purification, characterization and preliminary X-ray crystallographic studies of monodehydroascorbate reductase from Oryza sativa L. japonica - Do, Hackwon (International Union of Crystallography, 2014)

(untitled)
Monodehydroascorbate reductase (MDHAR; EC 1.6.5.4) is a key enzyme in the reactive oxygen species (ROS) detoxification system of plants. The participation of MDHAR in ascorbate (AsA) recycling in the ascorbate–glutathione cycle is important in the acquired tolerance of crop plants to abiotic environmental stresses. Thus, MDHAR represents a strategic target protein for the improvement of crop yields. Although physiological studies have intensively characterized MDHAR, a structure-based functional analysis is not available. Here, a cytosolic MDHAR (OsMDHAR) derived from Oryza sativa L. japonica was expressed using Escherichia coli strain NiCo21 (DE3) and purified. The purified OsMDHAR showed specific enzyme activity (approximately 380 U per milligram of protein) and was crystallized using the hanging-drop vapour-diffusion method at pH 8.0 and 298 K. The crystal diffracted to 1.9 Å resolution and contained one molecule in the asymmetric unit (the Matthews coefficient V (M) is 1.98 Å(3) Da(−1), corresponding to a solvent content of 38.06%) in space group P4(1)2(1)2 with unit-cell parameters a = b = 81.89, c = 120.4 Å. The phase of the OsMDHAR structure was resolved by the molecular-replacement method using a ferredoxin reductase from Acidovorax sp. strain KKS102 (PDB entry 4h4q) as a model.